Lying in Competitive Environments: A Clean Identification of Behavioral Impacts - Simon Dato; Eberhard Feess; Petra Nieken (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the last decade, forced ranking systems where employees' bonuses depend on their rank assigned by superiors have become less popular. Whereas the inherently competitive structure of ranking systems provides high effort incentives, it might also increase incentives for misconduct. Previous literature supports this view by demonstrating that, as compared to individual incentive schemes, highly competitive environments are associated with higher degrees of lying and cheating. However, it is not clear if this is driven by stronger financial incentives arising from the high marginal benefit from winning a competition, and/or the behavioral impacts of competition. Psychologically, a competitive environment alters incentives for misconduct via (i) the negative payoff externality that winning imposes on competitors, and (ii) a desire to win, i.e., succeeding in a competition is valuable per se. We design an experiment that allows us to disentangle financial and psychological incentives for misconduct and decompose the behavioral impacts. Our results provide clean evidence of a significant lying-enhancing desire-to-win-effect and an insignificant lying-reducing negative externality effect.
Keywords: C90; D82; D91; 330; private information; lying; contest; competition; cheating